2019
DOI: 10.1016/j.ijcha.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Very late presentation in ST elevation myocardial infarction: Predictors and long-term mortality

Abstract: Background Despite improvements in ST elevation myocardial infarction (STEMI) care, total ischemic time remains long in patients who present late. Our goal was to identify predictors of very late presentation (≥12 h) of STEMI and determine long-term mortality. Methods We retrospectively examined consecutive patients admitted with STEMI to our institution using the ACTION Registry™. Time of symptom onset to first medical contact (FMC) was calculated and categorized as <1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 18 publications
2
33
1
1
Order By: Relevance
“…Similarly, study conducted by Khan JA et al [11] reported that The key cause for delayed arrival at hospital(49 %) was misunderstanding of symptoms, after that seeking a local healthcare professional (25%), residing in an region away from a hospital facility (10%), waiting for the disappearance of symptoms with home care (8 percent), scarcity of transportation (4%) and lacking an attendant to take the patient towards hospital (4%). However, study conducted by McNair PW et al [12] reported that diabetes, feminine gender, and lack of Angina were closely linked to late presentation in their multivariable study. (c-statistic = 0.70).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, study conducted by Khan JA et al [11] reported that The key cause for delayed arrival at hospital(49 %) was misunderstanding of symptoms, after that seeking a local healthcare professional (25%), residing in an region away from a hospital facility (10%), waiting for the disappearance of symptoms with home care (8 percent), scarcity of transportation (4%) and lacking an attendant to take the patient towards hospital (4%). However, study conducted by McNair PW et al [12] reported that diabetes, feminine gender, and lack of Angina were closely linked to late presentation in their multivariable study. (c-statistic = 0.70).…”
Section: Discussionmentioning
confidence: 90%
“…Pre-hospital time delay is an important factor in STEMI, which lowers the probability of revascularization as well as increases mortality [1]. Despite advances in STEMI treatment, in late presenting patients, total ischemic timeframe remains prolonged [7]. Although, the objective of STEMI is to minimize infarct duration, negative outcomes, and death through timely and full coronary reperfusion through primary coronary angioplasty (PCI) or fibrinolysis [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although AMI patients with late hospital presentation have a high incidence of acute complications and poor outcomes even in the primary PCI era [2], current guidelines do not necessarily recommend primary PCI in patients with AMI with ST-segment elevation who present later than 12 h from symptom onset [3]. In AMI patients with late presentation, the search for acute complications on admission and careful observation in the acute phase is more important than in patients with successful early reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Another predictor for outcome after MI is the time of presentation after the index event. Female sex, diabetes, and absence of chest pain are strong predictors of presentation delay, and long-term mortality is significantly increased in those presenting very late [40]. If early percutaneous catheter interventions are not possible, fibrinolysis is commonly used as the first treatment strategy in patients with acute ST-elevation MI.…”
Section: Coronary Artery Disease and Myocardial Infarctionmentioning
confidence: 99%